2021
DOI: 10.1371/journal.pone.0258136
|View full text |Cite
|
Sign up to set email alerts
|

Demographic responses of a threatened, low-density ungulate to annual variation in meteorological and phenological conditions

Abstract: As global climate change progresses, wildlife management will benefit from knowledge of demographic responses to climatic variation, particularly for species already endangered by other stressors. In Canada, climate change is expected to increasingly impact populations of threatened woodland caribou (Rangifer tarandus caribou) and much focus has been placed on how a warming climate has potentially facilitated the northward expansion of apparent competitors and novel predators. Climate change, however, may also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…However, there may also be more opaque, indirect explanations for these lagged effects. Although 1‐year lagged effects have only been shown in primates due to rainfall and the El Niño climate oscillation ( Brachyteles hypoxanthus and Lagothrix lagothricha : Wiederholt & Post, 2011 ), lagged effects from temperature have been found in a variety of montane and grassland mammals including on population growth in American bison ( Bison bison : Koons et al, 2015 ) and adult female survival and juvenile recruitment in woodland caribou ( Rangifer tarandus caribou : DeMars et al, 2021 ). Willisch et al ( 2013 ) found that higher winter air temperatures corresponded to decreased survival in adult males and yearlings in alpine chamois ( Rupicapra rupicapra ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there may also be more opaque, indirect explanations for these lagged effects. Although 1‐year lagged effects have only been shown in primates due to rainfall and the El Niño climate oscillation ( Brachyteles hypoxanthus and Lagothrix lagothricha : Wiederholt & Post, 2011 ), lagged effects from temperature have been found in a variety of montane and grassland mammals including on population growth in American bison ( Bison bison : Koons et al, 2015 ) and adult female survival and juvenile recruitment in woodland caribou ( Rangifer tarandus caribou : DeMars et al, 2021 ). Willisch et al ( 2013 ) found that higher winter air temperatures corresponded to decreased survival in adult males and yearlings in alpine chamois ( Rupicapra rupicapra ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential impacts are not restricted to winter. Juvenile recruitment has been negatively correlated to warmer growing seasons that lead to early plant senescence in autumn (DeMars et al, 2021), an important period of resource acquisition for capital breeders such as caribou. Although current impacts from these direct mechanisms are likely secondary to the other more indirect mechanisms previously discussed (e.g., apparent competition), there is considerable uncertainty as to how the magnitude of these direct impacts may change as climate change progresses (DeMars et al, 2021).…”
Section: Mechanisms Associated With Climate Changementioning
confidence: 99%
“…According to several studies, however, climate appears to be the most relevant factor for several taxa at large scales [2][3][4][5]. In recent decades, it has been demonstrated that the global climate is becoming warmer [6], with widespread effects on biological systems [7][8][9][10]. This recent climate change has already affected the distribution of many species [11][12][13][14] and is modifying the margins of their distributions over short periods of time [15][16][17].…”
Section: Introductionmentioning
confidence: 99%